Composite material for removing formaldehyde as well as preparation method and application of composite material

By preparing Prussian blue nanoparticles-like composite materials with wood or bamboo under solvothermal method and hydrothermal conditions, and pyrolytic treatment is carried out, the problems of low formaldehyde removal efficiency and secondary pollution in the prior art are solved, and high efficiency is achieved. Environmentally friendly formaldehyde removal effects, suitable for home and wider environmental improvements.

CN119186501APending Publication Date: 2024-12-27ZHEJIANG FORESTRY UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411444026.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The prior art is not efficient in removing formaldehyde pollution, which may cause secondary pollution, and has a limited scope of use, making it difficult to meet the improvement needs of indoor and outdoor environments.

Method used

Prussian blue-like nanoparticles were prepared by one-step solvothermal method, and the alkali-pretreated wood or bamboo was reacted with them under hydrothermal conditions, and then subjected to pyrolysis to prepare a composite material that efficiently removes formaldehyde.

Benefits of technology

This method provides an efficient and environmentally friendly formaldehyde removal method, which can significantly reduce indoor formaldehyde concentration, improve air quality, and reduce performance in multiple cycle adsorption, which is suitable for a wide range of environmental improvements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186501A_ABST
    Figure CN119186501A_ABST
Patent Text Reader

Abstract

The invention discloses a composite material for removing formaldehyde as well as a preparation method and application of the composite material. Prussian blue-like nanoparticles are prepared by adopting a one-step solvothermal method; adding wood or bamboo subjected to alkali pretreatment into the Prussian blue-like nanoparticle solution obtained in the step (1), and reacting under a hydrothermal condition; and pyrolyzing the obtained wood or bamboo wood modified by the prussian blue-like nano particles at 400-900 DEG C to obtain the composite material for removing formaldehyde.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials, and in particular relates to a composite material for removing formaldehyde, a preparation method and an application thereof. Background Art

[0002] In recent years, as the problem of indoor air pollution has become increasingly prominent, formaldehyde pollution has become a focus of attention. Formaldehyde is a highly irritating toxic gas that is commonly found in building materials and furniture, especially in wood products containing adhesives. Long-term exposure to formaldehyde poses a major threat to human health and may cause eye discomfort, upper respiratory tract irritation, and even serious lung disease or cancer. Therefore, the development of materials that can effectively remove indoor formaldehyde has become an urgent need in the field of environmental governance.

[0003] At present, the treatment methods for formaldehyde pollution on the market mainly include physical adsorption, chemical neutralization and biological methods. The physical adsorption method mainly uses adsorbents such as activated carbon. Although it can quickly adsorb formaldehyde, it is easily saturated and difficult to regenerate. The chemical neutralization method uses chemical substances to react to neutralize formaldehyde, but the residual chemical substances may cause secondary pollution. The biological method uses plant or microbial metabolism to degrade formaldehyde, but the efficiency is relatively low and it is difficult to meet practical needs. In addition, existing formaldehyde removal products can often only deal with pollution in indoor spaces, but are not applicable to a wider range of environments.

[0004] In summary, the existing technology still has problems such as low removal efficiency, possible secondary pollution, and limited scope of use. Therefore, the development of a new type of biomass-based composite material can not only provide an environmentally friendly and efficient formaldehyde removal method, but also broaden the scope of application and provide a safer and more reliable indoor and outdoor environment improvement solution. Summary of the invention

[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and to briefly introduce some preferred embodiments.

[0006] As one aspect of the present invention, the present invention provides a method for preparing a composite material for removing formaldehyde, which comprises the following steps:

[0007] (1) Prussian blue-like nanoparticles were prepared by a one-step solvothermal method;

[0008] (2) adding the alkali-pretreated wood or bamboo to the Prussian blue-like nanoparticle solution obtained in step (1) to react under hydrothermal conditions;

[0009] (3) Pyrolyzing the wood or bamboo modified with the Prussian blue-like nanoparticles obtained in step (2) at 400-900° C. to obtain a composite material for removing formaldehyde.

[0010] As a preferred embodiment of the method for preparing the composite material for removing formaldehyde of the present invention: in step (2), the temperature of the hydrothermal condition is 45 to 85° C. and the time is 2 to 8 hours.

[0011] As a preferred embodiment of the method for preparing the composite material for removing formaldehyde of the present invention: in step (2), the mass ratio of the Prussian blue nanoparticles to the wood or bamboo is 0.2 to 1:1.

[0012] As a preferred embodiment of the method for preparing the composite material for removing formaldehyde described in the present invention: in step (2), the alkali pretreatment includes immersing the wood or bamboo into an alkali solution, the mass concentration of the alkali solution is 5-15%, the mass ratio of the wood to the alkali solution is 1:10-25, and the alkali includes sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate or ammonia water.

[0013] As a preferred embodiment of the method for preparing the composite material for removing formaldehyde of the present invention: in step (3), the pyrolysis temperature is 500-600° C. and the time is 12-24 hours.

[0014] As a preferred embodiment of the method for preparing the composite material for removing formaldehyde described in the present invention: in step (1), the Prussian blue-like nanoparticles include one of FeCo-PBA, CoCo-PBA, FeFe-PBA, MnFe-PBA, CdCo-PBA, and NiFe-PBA.

[0015] Preferably, the preparation of Prussian blue-like nanoparticles adopts a one-step solvothermal method, and the specific preparation method is as follows:

[0016] (1) Accurately weigh 0.332 g of K4[Co(CN)6]·3H2O and dissolve it in 200 mL of deionized water. Stir it magnetically at room temperature for 10 min to completely dissolve it. Weigh 6 g of polyvinyl pyrrolidone (PVP) and add it to the above solution. Continue stirring for 20 min until PVP is completely dissolved to obtain solution A.

[0017] (2) Take another beaker, weigh 0.21 g FeSO4·7H2O and 0.187 g Co(CH3COO)2·4H2O, and dissolve them in 200 mL deionized water to obtain solution B;

[0018] (3) Solution B was added to solution A at a uniform rate using a peristaltic pump and stirred continuously at room temperature for 24 h. Fe-CoPBA nanoparticles were obtained after stirring at room temperature for 24 h. The precipitate was collected by centrifugation, washed three times with deionized water and anhydrous ethanol, and dried in a vacuum drying oven at 60 °C to obtain Fe-CoPBA nanoparticles of uniform size (nanosphere morphology, average particle size of 260 nm, specific surface area of ​​700-950 m2 / g);

[0019] The present invention also relates to a bamboo-based or wood-based composite material for removing formaldehyde and a preparation method thereof, wherein the specific process steps are as follows:

[0020] (1) 0.4 g of Fe-CoPBA powder was ultrasonically dispersed in 20 mL of deionized water;

[0021] (2) adding bamboo chips or wood chips (1.5 cm*1.5 cm*0.2 cm) pretreated with sodium hydroxide to the above solution and stirring at 45-85° C. for 2-8 hours;

[0022] (3) After cooling to room temperature, the mixture is placed in an oven and dried at 60° C. for 6 to 12 hours to obtain a bamboo-based or wood-based composite material having formaldehyde removal performance;

[0023] (4) The obtained bamboo-based or wood-based composite material is subjected to pyrolysis treatment in a tube furnace at 400-900° C. for 12-24 h to obtain a carbonaceous bamboo-based or wood-based composite material (carbonaceous material, specific surface area 600-700 m 2 / g).

[0024] Beneficial effects of the invention: The invention uses green and environmentally friendly biomass materials such as wood and bamboo to compound with Prussian blue-like nanoparticles to obtain wood-based or bamboo-based composite materials, which overcomes the shortcomings of the existing composite material preparation method being complicated and having poor formaldehyde removal effect, and provides a new composite material for removing harmful gases such as formaldehyde. Using it as a source material for home use will help reduce other content of formaldehyde in homes, improve the indoor air quality of homes, and protect human health. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the following briefly introduces the drawings required for describing the embodiment, wherein:

[0026] Figure 1 This is a scanning electron microscope image of the wood-based composite material prepared in Example 1.

[0027] Figure 2 This is the N2 adsorption / desorption isotherm of the wood-based composite material prepared in Example 1.

[0028] Figure 3 This is the pore size distribution of the wood-based composite material prepared in Example 1.

[0029] Figure 4 This is the formaldehyde removal effect of the wood-based composite materials prepared in Examples 1 to 6.

[0030] Figure 5This is a diagram showing the formaldehyde cyclic adsorption effects of the prepared wood-based composite materials. DETAILED DESCRIPTION

[0031] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments.

[0032] Embodiment 1:

[0033] (1) Accurately weigh 0.332 g of K4[Co(CN)6]·3H2O and dissolve it in 200 mL of deionized water. Stir it magnetically at room temperature for 10 min to completely dissolve it. Weigh 6 g of polyvinylpyrrolidone (PVP) (average molecular weight 58,000, K30, viscosity range 0.6-1.0 mPa·s) and add it to the above solution. Continue stirring for 20 min until PVP is completely dissolved to obtain solution A.

[0034] (2) In another beaker, weigh 0.21 g FeSO4·7H2O and 0.187 g Co(CH3COO)2·4H2O and dissolve them in 200 mL deionized water to obtain solution B.

[0035] (3) Add solution B to solution A at a uniform rate using a peristaltic pump and continue stirring at room temperature for 24 h;

[0036] (4) centrifuging the solution obtained in step (3) at 8000 r / min for 8 minutes;

[0037] (5) collecting the precipitate, washing the precipitate with deionized water and anhydrous ethanol three times, and drying it in a vacuum drying oven at 60° C. to obtain Fe-CoPBA nanoparticles of uniform size;

[0038] (6) 0.4 g of Fe-CoPBA nanoparticle powder was ultrasonically dispersed in 20 mL of deionized water, 0.4 g of bamboo or wood (1.5 cm*1.5 cm*0.2 cm) pretreated with sodium hydroxide was added, and the mixture was stirred at 65 °C for 4 h, and then cooled to room temperature to obtain a Fe-CoPBA-modified bamboo-based or wood-based composite material with formaldehyde removal performance;

[0039] The sodium hydroxide pretreatment method for bamboo or wood is as follows: immersing the bamboo or wood in a 10wt% sodium hydroxide aqueous solution, with a solid-liquid ratio of 1:20, an immersion time of 30 minutes, and a reaction temperature of 30°C to obtain the pretreated bamboo or wood.

[0040] (7) The bamboo-based or wood-based composite material obtained above was placed in a tubular furnace for pyrolysis at 500° C. for 16 h to obtain a carbonaceous bamboo-based or wood-based composite material, which was named FeCo4CA.

[0041] (8) The carbonaceous wood-based (poplar) composite material obtained in step (7) is measured using closed experimental containers. At room temperature of 25 degrees Celsius, the diluted formaldehyde standard solution and formaldehyde detection equipment are placed on a square glass platform, and then the experimental device is sealed. Let it stand for 2 hours until the formaldehyde evaporates into the container, so that the value of the formaldehyde detection equipment stabilizes at a formaldehyde concentration of 0.4g / L. Subsequently, the carbonaceous wood-based composite material is placed in the device through the reserved window, and the device is immediately sealed. The weight of the adsorbent material before placement and 8 hours later is recorded, and the data recorded by the formaldehyde detection equipment is analyzed. The carbonaceous wood-based composite material can remove approximately 40% of formaldehyde gas, see Figure 4 . And the cyclic adsorption test was carried out. After multiple adsorption cycles, the adsorption performance was only reduced by 10%. Figure 5 .

[0042] Figure 1 This is a scanning electron microscope photograph of the carbonaceous wood-based composite material of FeCo4CA prepared in Example 1. The adsorbent has a large amount of PBA loading on its surface, which is beneficial for capturing organic gases in the air.

[0043] Figure 2 The N2 adsorption-desorption isotherm of the carbonaceous wood-based composite material prepared in Example 1 is a Langmuir-iv type curve with an obvious hysteresis loop, which indicates that there are micropores and mesopores in the carbonaceous wood-based composite material. This shows that the microreactor has a hierarchical porous structure. These results are also consistent with the pore size distribution calculated by the Barrett-Joyner-Halenda (BJH) model (the average pore size distribution is 9nm). The pore size distribution of the adsorbent is as follows Figure 3 As mentioned above, it can be seen from the figure that the pore size of the adsorbent is distributed between 1 and 20 nm, which is a typical nanomaterial.

[0044] Embodiment 2:

[0045] Fe-CoPBA nanoparticles were prepared according to steps (1) to (5) of Example 1.

[0046] (6) 0.2 g of Fe-CoPBA nanoparticle powder was ultrasonically dispersed in 20 mL of deionized water, 0.4 g of bamboo or wood (1.5 cm*1.5 cm*0.2 cm) pretreated with sodium hydroxide was added, and the mixture was stirred at 65 °C for 4 h, and then cooled to room temperature to obtain a Fe-CoPBA-modified bamboo-based or wood-based composite material with formaldehyde removal performance;

[0047] (7) The bamboo-based or wood-based composite material obtained above was placed in a tubular furnace for pyrolysis at 500° C. for 16 h to obtain a carbonaceous bamboo-based or wood-based composite material, named FeCo2CA.

[0048] The formaldehyde adsorption effect of the carbon wood-based (poplar) composite material was tested in the same manner as in step (8) of Example 1. The carbon wood-based composite material can remove approximately 52% of the formaldehyde gas. Figure 4 . And the cyclic adsorption test was carried out. After multiple adsorption cycles, the adsorption performance was only reduced by about 10%. Figure 5 .

[0049] Embodiment 3:

[0050] Fe-CoPBA nanoparticles were prepared according to steps (1) to (5) of Example 1.

[0051] (6) 0.1 g of Fe-CoPBA nanoparticle powder was ultrasonically dispersed in 20 mL of deionized water, 0.4 g of bamboo or wood (1.5 cm*1.5 cm*0.2 cm) pretreated with sodium hydroxide was added, and the mixture was stirred at 65 °C for 4 h, and then cooled to room temperature to obtain a Fe-CoPBA-modified bamboo-based or wood-based composite material with formaldehyde removal performance;

[0052] (7) The bamboo-based or wood-based composite material obtained above was placed in a tubular furnace for pyrolysis at 500° C. for 16 h to obtain a carbonaceous bamboo-based or wood-based composite material, which was named FeCo1CA.

[0053] The formaldehyde adsorption effect of the carbonaceous wood-based (poplar wood) composite material was tested in the same manner as in step (8) of Example 1. The carbonaceous wood-based composite material can remove approximately 40% of the formaldehyde gas. Figure 4 .

[0054] Embodiment 4:

[0055] (1) Accurately weigh 0.332 g of K4[Co(CN)6]·3H2O and dissolve it in 200 mL of deionized water. Stir it magnetically at room temperature for 10 min to completely dissolve it. Weigh 6 g of polyvinyl pyrrolidone (PVP) and add it to the above solution. Continue stirring for 20 min until PVP is completely dissolved to obtain solution A.

[0056] (2) In another beaker, weigh 0.387 g of Co(CH3COO)2·4H2O and dissolve it in 200 mL of deionized water to obtain solution B.

[0057] (3) Add solution B to solution A at a uniform rate using a peristaltic pump and continue stirring at room temperature for 24 h;

[0058] (4) centrifuging the solution obtained in step (3) at 8000 r / min for 8 minutes;

[0059] (5) collecting the precipitate, washing it with deionized water and anhydrous ethanol three times, and drying it in a vacuum oven at 60°C to obtain Co-CoPBA nanoparticles of uniform size;

[0060] (6) 0.4 g of Co-CoPBA nanoparticle powder was ultrasonically dispersed in 20 mL of deionized water, and 0.4 g of bamboo or wood treated with sodium hydroxide was added to the solution and stirred at 65 °C for 4 h. The mixture was cooled to room temperature to obtain a Co-CoPBA-modified bamboo-based or wood-based composite material with formaldehyde removal performance.

[0061] (7) The bamboo-based or wood-based composite material obtained above was placed in a tube furnace for pyrolysis at 500° C. for 16 h to obtain a carbonaceous bamboo-based or wood-based composite material, which was named CoCo4CA.

[0062] The formaldehyde adsorption effect of the carbonaceous wood-based (poplar wood) composite material was tested in the same manner as in step (8) of Example 1. The carbonaceous wood-based composite material can remove approximately 48% of the formaldehyde gas. Figure 4 . And the cyclic adsorption test was carried out. After multiple adsorption cycles, the adsorption performance decreased by about 20%. Figure 5 .

[0063] Embodiment 5:

[0064] (1) Accurately weigh 0.332 g of K4[Co(CN)6]·3H2O and dissolve it in 200 mL of deionized water. Stir it magnetically at room temperature for 10 min to completely dissolve it. Weigh 6 g of polyvinyl pyrrolidone (PVP) and add it to the above solution. Continue stirring for 20 min until PVP is completely dissolved to obtain solution A.

[0065] (2) In another beaker, weigh 0.387 g of Co(CH3COO)2·4H2O and dissolve it in 200 mL of deionized water to obtain solution B.

[0066] (3) Add solution B to solution A at a uniform rate using a peristaltic pump and continue stirring at room temperature for 24 h;

[0067] (4) centrifuging the solution obtained in step (3) at 8000 r / min for 8 minutes;

[0068] (5) collecting the precipitate, washing it with deionized water and anhydrous ethanol three times, and drying it in a vacuum oven at 60°C to obtain Co-CoPBA nanoparticles of uniform size;

[0069] (6) 0.2 g of Co-CoPBA nanoparticle powder was ultrasonically dispersed in 20 mL of deionized water, and 0.4 g of bamboo or wood treated with sodium hydroxide was added to the solution and stirred at 65 °C for 4 h. The mixture was cooled to room temperature to obtain a Co-CoPBA-modified bamboo-based or wood-based composite material with formaldehyde removal performance.

[0070] (7) The bamboo-based or wood-based composite material obtained above was placed in a tubular furnace for pyrolysis at 500° C. for 16 h to obtain a carbonaceous bamboo-based or wood-based composite material, named CoCo2CA.

[0071] The formaldehyde adsorption effect of the carbon wood-based (poplar) composite material was tested in the same manner as in step (8) of Example 1. Figure 4 .

[0072] Embodiment 6:

[0073] (1) Accurately weigh 0.332 g of K4[Co(CN)6]·3H2O and dissolve it in 200 mL of deionized water. Stir it magnetically at room temperature for 10 min to completely dissolve it. Weigh 6 g of polyvinyl pyrrolidone (PVP) and add it to the above solution. Continue stirring for 20 min until PVP is completely dissolved to obtain solution A.

[0074] (2) In another beaker, weigh 0.387 g of Co(CH3COO)2·4H2O and dissolve it in 200 mL of deionized water to obtain solution B.

[0075] (3) Add solution B to solution A at a uniform rate using a peristaltic pump and continue stirring at room temperature for 24 h;

[0076] (4) centrifuging the solution obtained in step (3) at 8000 r / min for 8 minutes;

[0077] (5) collecting the precipitate, washing it with deionized water and anhydrous ethanol three times, and drying it in a vacuum oven at 60°C to obtain Co-CoPBA nanoparticles of uniform size;

[0078] (6) 0.1 g of Co-CoPBA nanoparticle powder was ultrasonically dispersed in 20 mL of deionized water, and 0.4 g of bamboo or wood treated with sodium hydroxide was added to the solution and stirred at 65 °C for 4 h. The mixture was cooled to room temperature to obtain a Co-CoPBA-modified bamboo-based or wood-based composite material with formaldehyde removal performance.

[0079] (7) The bamboo-based or wood-based composite material obtained above was placed in a tubular furnace for pyrolysis at 500° C. for 16 h to obtain a carbonaceous bamboo-based or wood-based composite material, which was named CoCo1CA.

[0080] The formaldehyde adsorption effect of the carbon wood-based (poplar) composite material was tested in the same manner as in step (8) of Example 1. Figure 4 .

[0081] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a composite material for removing formaldehyde, characterized in that: The following steps are involved: (1) Prussian blue-like nanoparticles were prepared by a one-step solvothermal method; (2) adding the alkali-pretreated wood or bamboo to the Prussian blue-like nanoparticle solution obtained in step (1) to react under hydrothermal conditions; (3) Pyrolyzing the wood or bamboo modified with the Prussian blue-like nanoparticles obtained in step (2) at 400-900° C. to obtain a composite material for removing formaldehyde.

2. The method for preparing a composite material for removing formaldehyde according to claim 1, characterized in that: In step (2), the temperature of the hydrothermal condition is 45 to 85° C. and the time is 2 to 8 hours.

3. The method for preparing the composite material for removing formaldehyde according to claim 1 or 2, characterized in that: In step (2), the mass ratio of the Prussian blue nanoparticles to the wood or bamboo is 0.2 to 1:

1.

4. The method for preparing a composite material for removing formaldehyde according to claim 1 or 2, characterized in that: In step (2), the alkali pretreatment comprises immersing the wood or bamboo in an alkali solution, the mass concentration of the alkali solution is 5-15%, the mass ratio of the wood to the alkali solution is 1:10-25, and the alkali comprises sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate or ammonia water.

5. The method for preparing the composite material for removing formaldehyde according to claim 1 or 2, characterized in that: In step (3), the pyrolysis temperature is 500-600° C. and the time is 12-24 hours.

6. The method for preparing a composite material for removing formaldehyde according to claim 1 or 2, characterized in that: In step (1), the Prussian blue-like nanoparticles include one of FeCo-PBA, CoCo-PBA, FeFe-PBA, MnFe-PBA, CdCo-PBA, and NiFe-PBA.

7. The method for preparing a composite material for removing formaldehyde according to claim 1 or 2, characterized in that: The average particle size of the Prussian blue-like nanoparticles is 200N400nm.

8. The composite material prepared by the method for preparing the composite material for removing formaldehyde according to claim 1.

9. Use of the composite material according to claim 8 in environmentally friendly furniture materials.